Effect of nanoclay on mechanical, flammability, and water absorption properties of glass fiber-epoxy composite. Issue 1 (31st December 2022) - Kowshik, Suhas; Shettar, Manjunath; Rangaswamy, Nikhil; Chate, Ganesh; Somdee, Patcharapon
Abstract: Automobile bodywork, wall insulation, bridges, and ship hulls, to name a few, are among the many applications for glass fiber-epoxy composites. To manufacture lightweight products for aforesaid applications, the properties of glass fiber-epoxy composites must be improved. The present work aims to fabricate and characterize nanoclay epoxy composites (NECs) and nanoclay glass fiber epoxy composites (NGFEC) by varying nanoclay weight percentages (i.e., 0, 2, and 4 wt.%). NECs are fabricated by a general-casting technique, and NGFECs are fabricated by hand layup technique. Flexural, impact, flammability, and water absorption tests are conducted to evaluate the properties of NECs and NGFECs in accordance with ASTM standards. The addition of nanoclay increases the flexural and impact strengths of NECs and NGFECs by 8 to 14% and 16 to 29%, respectively. Also, nanoclay additions decline the burning rate and water uptake (%) of NECs and NGFECs by 6 to 23% and 6 to 30%, respectively. The impact strength of pure epoxy, NECs, GFEC, and NGFEC is diminished by 7 to 25% at the end of 70 days of water absorption. Scanning electron microscopy images are employed to learn the causes of specimen failure under an impact load for as-made and water absorbed conditions. Crack deflection, pinning, and arresting, fiber pull-out, crazing and matrix rupturing, shear leaps are observed in the SEM images.